Supervision, Spiritual Care and People-Centred Healthcare: Proposing Interdisciplinary Partnerships to Support Holistic Care. Issue 4 (1st October 2016) - Dungan, Lynette
Abstract : This article reviews how good supervision can support people-centred health care and so contribute to the goals of practical theology and public health. Supervision is considered to be an interdisciplinary health promoting practice which can support, educate and empower. Supervision that accepts spiritual care as normative is able to partner with pastoral and healthcare practitioners seeking to offer holistic care. Partnerships are proposed between supervisors, spiritual care and health care practitioners and associated organizations, to mutually benefit supervision practice and health care practice.